THE CONCEPT OF MAHABBAH OF ABDUS SHAMAD AL-PALIMBANI IN FACING THE SPIRITUAL CRISIS OF MODERN MAN - Nur Hadi Ihsan; Amir Maliki Abitolkhah; Indah Maulidia Rahma (UIN Antasari Banjarmasin, 2022)
Modern man's spiritual crises is a fascinating topic that is constantly pertinent to be discussed nowadays. The promise of a remedy to this modern dilemmas is even more intriguing. Abdus Shamad al-Palimbani is a prominent Sufi figure in the Malay Indoneaian Archipelago, with Sufi mahabbah teaching that is favorable to resolving this spiritual crisis. This work aims to explore the notion of mahabbah of al-Palembani and its significance in overcoming modern humans' spiritual dilemmas. This study is library research using qualitative approach. The data wer collected utilizing documentary techniques referring to boks, articles, and other published materials. The acquired data is then analyzed employing the descriptive-analytical method. This study finds that according to Abdus Shamad, human love is divided into stages, starting with love for others, wealth, family and relations, self-love, and love for Allah and His Messenger. If a man is bound by the four worldly degrees of love, he will suffer a spiritual crisis. Only by achieving the ultimate level of love, mahabbatullah, can he discover his own self, both material and spiritual.